2017
DOI: 10.1021/acs.jpcb.7b05469
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Interactions Overcome Hydration to Drive the Collapse Transition of Gly15

Abstract: Simulations and experiments show oligo-glycines, polypeptides lacking any side chains, can collapse in water. We assess the hydration thermodynamics of this collapse by calculating the hydration free energy at each of the end points of the reaction coordinate, here taken as the end-to-end distance (r) in the chain. To examine the role of the various conformations for a given r, we study the conditional distribution, P(Rg|r), of the radius of gyration for a given value of r. The free energy change versus Rg, −k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 51 publications
5
68
1
Order By: Relevance
“…We thus find the solvation of the flexible alkane to be more favorable than that of the rigid alkane. Our findings are consistent with those of Pettitt and co-workers, who showed that the conformation of alkane chains and peptides can influence their hydration free energies substantially [66][67][68]. Our results also lend further support to the notion that surface-area models, which are commonly used to estimate the driving force of hydrophobic assembly, but are incapable of capturing subtle but important differences between the rigid and flexible solutes, are not appropriate for a quantitative treatment of hydrophobic hydration and interactions [66,69].…”
Section: B Hard-sphere Alkanesupporting
confidence: 93%
“…We thus find the solvation of the flexible alkane to be more favorable than that of the rigid alkane. Our findings are consistent with those of Pettitt and co-workers, who showed that the conformation of alkane chains and peptides can influence their hydration free energies substantially [66][67][68]. Our results also lend further support to the notion that surface-area models, which are commonly used to estimate the driving force of hydrophobic assembly, but are incapable of capturing subtle but important differences between the rigid and flexible solutes, are not appropriate for a quantitative treatment of hydrophobic hydration and interactions [66,69].…”
Section: B Hard-sphere Alkanesupporting
confidence: 93%
“…(ex) p , in this process is 32 ± 128 cal/mol-K -we use the c (ex) p [h(ex) ] values throughout. The uncertainty is necessarily high for reasons noted above, but focusing on the mean value, the trends suggest a positive contribution, just as was found Left panel: The hydration free energy of methane, following(2). With the expected opposition of long-range/attractive interactions to the other contributions, the unfavorable net hydration free energy (filled-pentagons) increases with increasing T , the classic hydrophobic inverse temperature behavior.…”
mentioning
confidence: 64%
“…The calculation of µ (ex) and its entropic T s (ex) and enthalpic h (ex) contributions follows earlier work [14][15][16][17][18]. Briefly [8,9,22], the excess chemical potential is given by βµ (ex) = ln e βε , averaging ε over the binding energy distribution P (ε).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…8). As already noted, the conditional binding energy distribution is Gaussian to an excellent approximation [5][6][7][8]. The binding energy ε is a sum of van der Waals, ε vdW , and electrostatic, ε elec , contributions.…”
Section: Long-range Contributionsmentioning
confidence: 99%